2020
DOI: 10.1038/s41598-020-78898-8
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi protect tomato and nightshade plants against Tuta absoluta (Lepidoptera: Gelechiidae) through a hidden friendship and cryptic battle

Abstract: Endophytic fungi live within plant tissues without causing any harm to the host, promote its growth, and induce systemic resistance against pests and diseases. To mitigate the challenging concealed feeding behavior of immature stages of Tuta absoluta in both tomato (Solanum lycopersicum) and nightshade (Solanum scabrum) host plants, 15 fungal isolates were assessed for their endophytic and insecticidal properties. Twelve isolates were endophytic to both host plants with varied colonization rates. Host plants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 76 publications
(113 reference statements)
2
47
0
Order By: Relevance
“…Similarly, temperatures above 36 • C did not support the growth of B. bassiana. The maximum temperature recorded during the entire experimental period of the current study was 34 • C, during the month of May, with low relative humidity, which was conducive for the fungal growth [63]. Thus, B. bassiana was found to be an effective bio-pesticide for managing T. absoluta on tomato in Andhra Pradesh conditions, as well as in other locations in India that have similar agro-climatic conditions.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, temperatures above 36 • C did not support the growth of B. bassiana. The maximum temperature recorded during the entire experimental period of the current study was 34 • C, during the month of May, with low relative humidity, which was conducive for the fungal growth [63]. Thus, B. bassiana was found to be an effective bio-pesticide for managing T. absoluta on tomato in Andhra Pradesh conditions, as well as in other locations in India that have similar agro-climatic conditions.…”
Section: Discussionmentioning
confidence: 63%
“…Similar studies have also shown the negative systemic effects of endophytes on different life parameters of several insects. H. lixii F3ST1 caused the lower pupation, emergence, and survival of L. huidobrensis in Vicia faba (Akutse et al, 2013), reduced the oviposition and mining activity of T. absoluta in both S. scabrum and S. lycopersicum (Agbessenou et al, 2020), and reduced the feeding and oviposition of Thrips tabaci (Lindeman) (Thysanoptera: Thripidae) in Allium cepa (Muvea et al, 2014). Trichoderma asperellum M2RT4 is also reported to have a negative effect on the development and reproduction of Acyrthosiphon pisum (Harris) (Homoptera: Aphididae) in V. faba (Akello and Sikora, 2012), while S. lycopersicum inoculated with B. bassiana caused the lower oviposition and feeding by B. tabaci (Wei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The survival analysis based on the Kaplan-Meier product-limit method was used to determine the survival probability functions of the adults and progeny exposed to different fungal treatments and controls. The survival function curves for different fungal treatments and the controls were compared using the log-rank test (Agbessenou et al, 2020). The plant height, leaf length, leaf width, and shoot weight were analysed using ANOVA, and the differences in means were separated using the Student-Newman-Keuls (SNK) test.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial taxa like Colwelliaceae 10 , 63 Flavobacterium, Arthrobacter, Serratia, Bacillus, Enterobacter, Vibrio 64 , Pseudoalteromonas 63 and Achromobacter 65 produce chitinase. The presence of chitinase gene in CAB is unsurprising, as their foregut and hindgut are both made up of chitin 11 .…”
Section: Discussionmentioning
confidence: 99%